Assessment of a prototype for the Systemization of Nursing Care on a mobile device - Laura Cristhiane Mendonça Rezende; Sérgio Ribeiro dos Santos; Ana Lúcia Medeiros (Universidade de São Paulo, 2016)
Abstract Objectives: assess a prototype for use on mobile devices that permits registering data for the Systemization of Nursing Care at a Neonatal Intensive Care Unit. Method: an exploratory and descriptive study was undertaken, characterized as an applied methodological research, developed at a teaching hospital. Results: the mobile technology the nurses at the Neonatal Intensive Care Unit use was positive, although some reported they faced difficulties to manage it, while others with experience in using mobile devices did not face problems to use it. The application has the functions needed for the Systematization of Nursing Care at the unit, but changes were suggested in the interface of the screens, some data collection terms and parameters the application offers. The main contributions of the software were: agility in the development and documentation of the systemization, freedom to move, standardization of infant assessment, optimization of time to develop bureaucratic activities, possibilities to recover information and reduction of physical space the registers occupy. Conclusion: prototype software for the Systemization of Nursing Care with mobile technology permits flexibility for the nurses to register their activities, as the data can be collected at the bedside.